Association between Screen Time and Sleep Disorders in Teens with ADHD - Shahzad, Hafiz Muhammad; Punshi, Monica; Sualeh, Zumaira; Bukhari, Aliza; Sualeh, Yousra; Ahmad, Syed Iftikhar (Journal of Neonatal Surgery, 2025)
Background: To evaluate’ the association between daily screen time and sleep disturbances among adolescents with ADHD’. Methods: A cross-sectional study was conducted from June 2023 to May 2024, involving 81 adolescents aged 13 to 19 years diagnosed with ADHD. Data were collected using structured questionnaires addressing demographics, ADHD characteristics, screen exposure habits, and sleep-related outcomes. Associations between screen time variables and sleep disturbances were analyzed using chi-square tests, with significance set at p < 0.05. Results: Among participants, 65.4% reported screen use exceeding four hours daily, and 64.2% experienced sleep-related complaints. High screen exposure was significantly associated with sleep onset latency greater than 30 minutes (p = 0.009), daytime fatigue (p = 0.026), and diagnosed sleep disturbances (p = 0.005). Screen use within one hour before bedtime was also strongly correlated with delayed sleep onset. Conclusion: Viewing screens to excess, especially in the hours leading up to sleep, is associated with increased sleep problems in adolescents with ADHD. This set of findings emphasizes the necessity of specific behavioral intervention to manage digital media use within this at-risk population.